2022
DOI: 10.3390/electronics11213588
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model to Predict Stock Closing Price Using Novel Features and a Fully Modified Hodrick–Prescott Filter

Abstract: Forecasting stock market prices is an exciting knowledge area for investors and traders. Successful predictions lead to high financial revenues and prevent investors from market risks. This paper proposes a novel hybrid stock prediction model that improves prediction accuracy. The proposed method consists of three main components, a noise-filtering technique, novel features, and machine learning-based prediction. We used a fully modified Hodrick–Prescott filter to smooth the historical stock price data by remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Utilizing Bi-LSTM and GRU networks, the proposed model outperforms other models. In [17], a hybrid stock prediction model was presented. The model comprises a noise-filtering approach, unique features, and a prediction based on machine learning.…”
Section: Related Workmentioning
confidence: 99%
“…Utilizing Bi-LSTM and GRU networks, the proposed model outperforms other models. In [17], a hybrid stock prediction model was presented. The model comprises a noise-filtering approach, unique features, and a prediction based on machine learning.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Wanjawa & Muchemi have suggested that Artificial Neural Networks are capable of predicting stock prices on typical markets [5]. Ilyas et al argue that a method combining noise filtering technology, new features, and machine learning-based prediction can achieve low error and high accuracy in predicting stock closing prices [6]. Additionally, according to Hossain et al, by combining technical analysis with Belief Rule-Based Expert Systems (BRBES) and the Bollinger Band concept, people can predict stock prices for the next five days [7].…”
Section: Introductionmentioning
confidence: 99%